In search of the enemy: representations of the war scenario of the Malvinas’ war in the new textbooks (2006-present) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
The Malvinas war, far from being a fact of the recent past homogeneously crystallized in that complex called collective memory, is an issue that gets through a whole society and persists in the dispute over meanings. Historically, the school institution has played an essential role in this dispute, building prevailing ties with the national identity in general and with Malvinas Island in particular. However, these relationships and discourses have not been static and homogeneous, but have been modified according to the new schemes, norms and rules of current historical time. In this work we propose to analyze the representations of the Malvinas war scene in this fundamental part of the social structured based on the textbook as an object of study, during the new period inaugurated by the National Education Law (LEN). Starting from the notion of social discourse, we will review the representations of the contenders of the War and how they contribute to signify History.
Keywords: Malvinas War; social discourse; textbooks; history teaching; editorial proposals